Par-delà Nietzsche - Victor Kocay (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
This article presents Nietzsche's notion of the Übermensch (le surhomme in French) as a development of romanticism conceived of as a quest to reveal the sentiment that defines or characterizes each individual as an individual. This approach reveals the affinities between Nietzsche and Schopenhauer, notably with respect to Schopenhauer's notion of Will that Nietzsche transforms into that of the Will to power, thereby underscoring what can be considered as Nietzsche's individualism. We argue that as a romantic notion, the notion of Übermensch fashions an ideal of what life could be but overlooks the importance of otherness and the role that otherness plays in defining the individual. Going beyond Nietzsche implies that the Übermensch, as a logical construct neglects the desire to please that constitutes an important part of an individual's relation with otherness.